Burnout of Healthcare Workers and Its Implications for Hospital Organizational Performance: A Systematic Literature Review - Muhammad Ilham Surya Samawa; Nenny Hendajany; Nadiya Fitri Ningsih; Larasati Restu Dewayani; PPT Muhammad Rabbani PASA; Muhammad Yurisrakha AlRasyid (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to systematically review the literature on healthcare worker burnout and its implications for hospital organizational performance. It examines the role of Human Resource Management (HRM) practices and leadership effectiveness in influencing burnout and proposes three hypotheses: HRM practices significantly influence burnout, leadership effectiveness significantly influences burnout, and burnout significantly affects hospital organizational performance. Research Method: This study employed a Systematic Literature Review (SLR) based on PRISMA guidelines. Peer-reviewed articles published between 2020 and 2026 in English and Indonesian were retrieved from Scopus, Web of Science, ScienceDirect, PubMed, ProQuest, and Google Scholar. The selected studies focused on healthcare worker burnout in hospital settings and were analyzed using a structured review matrix and thematic synthesis guided by the JD-R Model, Social Exchange Theory, Organizational Support Theory, and COR Theory. Results and Discussion: The findings show that effective HRM practices and supportive, transformational, and caring leadership reduce burnout among healthcare workers. Burnout negatively affects hospital performance through lower productivity, reduced service quality, higher turnover intention, and weaker workforce retention. Implications: The study highlights the need for employee-centered HRM, supportive leadership, and well-being policies to improve hospital performance. Originality: This study positions burnout as a strategic organizational issue by integrating HRM, leadership, and performance perspectives in hospital management research.